PENINGKATAN SHOOTING MELALUI APLIKASI HOME WORKOUT PADA PESERTA EKSTRAKURIKULER FUTSAL PUTRI SMP ISLAM CIBUNGUR - Moh. Padli Pauji; Alfian Nur Hakim; Rizky Hanipan; Rafdlal Saeful Bakhri; Debi Krisna Irawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low shooting ability of the female futsal extracurricular participants of Cibungur Islamic Junior High School. The purpose of this study is to determine the increase in shooting through the home workout application in the female futsal extracurricular participants of Cibungur Islamic Junior High School. The type of research used in this study is quantitative research. The population used in this study is 40 extracurricular futsal participants for Cibungur Islamic Junior High School, sampling using purposive sampling techniques with female sample criteria, aged 13 - 15 years, routinely participating in the exercises carried out, there are core players from the female futsal extracurricular participants of Cibungur Islamic Junior High School, ready to follow all the instructions given by the researcher. The research instrument used was the shooting test. The data analysis technique used an assumption test and a hypothesis test. Based on the results of statistical calculations with a paired sample t test, a Sig. (2-sided) value of 0.000 was obtained. According to the test criteria if the value of Asymp. Sig. (2-sided) < 0.05 (sig 5%) then Ho was rejected and Ha was accepted, it can be concluded that there is a significant increase through the home workout application to the increase in shooting in the women's futsal extracurricular participants of Cibungur Islamic Junior High School.